Effective Use of Application Package Programs in Organizing Mathematics Lessons - Khakimdzhanova Shakhnoza Mirrakhimovna (Global Scientific Publishing, 2023)
This article presents scientific views on the importance of information technology in mathematics. Scientific opinions are concluded based on facts
Keywords: math; science; technology; logic